DEEP LEARNING DALAM PEMBELAJARAN MI TINJAUAN LITERATUR DALAM MEANINGFUL LEARNING MINDFUL LEARNING DAN JOYFUL LEARNING - Dewi, Aura Rahma; Maily, Mulia Eka Wati; Safitri, Frista Nur Cahyani; Zaitunnah, Putri Nor; Mala, Zahrotul Laili; Suttrisno, Suttrisno (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The low level of active engagement and meaningful learning among Madrasah Ibtidaiyah (MI) students highlights the need for a deeper and more contextualized learning approach. This study aims to examine the application of deep learning in MI education through three core approaches: meaningful learning, mindful learning, and joyful learning. The method employed is a literature review of 18 relevant national and international scholarly articles, analyzed thematically to explore implementation patterns, instructional strategies, and their impact on student learning outcomes. The findings reveal that the integration of these three approaches enhances student engagement, strengthens connections between subject matter and real-life contexts, and fosters reflective and enjoyable learning awareness. It is concluded that deep learning contributes positively to creating active, contextual, and meaningful learning in MI settings. The implication is that MI teachers need to design learning activities that promote deep understanding, self-awareness, and a joyful, collaborative learning environment.